Molecular Iodine Assisted Electrocyclisation: Synthesis of Arcyriaflavin A and Formal Synthesis of Staurosporinone - Torney, Prachi; Shirsat, Rajendra; Tilve, Santosh (Synlett, 2014)
A new method for the synthesis of the indolocarbazole alkaloid arcyriaflavin A is described. The synthetic strategy employs a graphite-catalysed alkenation, one-pot oxidation–Wittig reaction, iodine-catalysed electrocyclisation and nitrene insertion as the key steps. The strategy also constitutes a formal synthesis of another indolocarbazole alkaloid staurosporinone.
Keywords: indolocarbazole; electrocyclisation; iodine; aromatisation; graphite; domino